Human Islet Cell Transplantation Successful in Patients with Type 1 Diabetes Who Have SH - Mann, Kate (MD Conference Express, 2014)
This article discusses preliminary data from the Islet Transplantation in Type 1 Diabetes study [NCT00434811]. The Phase 3, open-label, single-group study was conducted by the Clinical Islet Transplantation (CIT) Consortium. The CIT was created by the National Institutes of Health to advance islet transplantation for patients with type 1 diabetes mellitus and severe hypoglycemia and patients who have had a kidney transplant.